(untitled) (Global Journal of Human-Social Science, 2023)
Bronze Age sites of the Southern Trans-Urals Sintashta Petrovka and Alakul archaeological cultures associated with the migrations of early Indo-European communities on the territory of Central Eurasia Since the 2000 an archaeological expedition of Chelyabinsk State University has been conducting research on Bronze Age sites near the modern village Stepnoye in the Chelyabinsk Region Russia The article presents the characteristics of the burial rite of the Bronze Age communities from the steppe region based on the analysis of 146 burials and sacrificial complexes The burial rituals of the studied sites demonstrate analogies to Indo-European mythological plots known from written sources and testify to the complex social processes that took place during this period The Sintashta and Petrovka series of burials shows the occurrence of elite groups of the population in society the Alakul series shows a return to the simplified stratification of the buried The most striking plots of the burial rite are burials in the position of embrace and burials with evidence of charioteering reflecting the symbolism of the Indo-European Twin myth